Stemodia maritima L. Extract Decreases Inflammation, Oxidative Stress, and Alveolar Bone Loss in an Experimental Periodontitis Rat Model - Teixeira, Alrieta H.; Freire, Jordânia M. de Oliveira; de Sousa, Luzia H. T.; Parente, Antônia T.; de Sousa, Nayara A.; Arriaga, Angela M. C.; Lopes da Silva, Francisca R.; Melo, Iracema M.; Castro da Silva, Igor I.; Pereira, Karuza M. A.; Goes, Paula; Costa, José J. do Nascimento; et al. (Frontiers in Physiology, 2017)
Periodontitis is very prevalent worldwide and is one of the major causes of tooth loss in adults. About 80% of the worldwide population use medicinal plants for their health care. Stemodia maritima L. (S. maritima) antioxidant and antimicrobial effects in vitro as well as anti-inflammatory properties. Herein, the potential therapeutic effect of S. maritima was assessed in rats subjected to experimental periodontitis (EP). EP was induced in female Wistar rats by nylon thread ligature around 2nd upper left molars for 11 days. Animals received (per os) S. maritima (0.2; 1 or 5 mg kg) or vehicle (saline+DMSO) 1 hour before ligature and then once daily for 11 days. The naive group had no manipulation. After this time-point, the animals were terminally anesthetized, and the maxillae were removed for morphometric and histological analyzes (HE). Gingival tissues were dissected to cytokine levels detection (TNF-α, IL1-β, CINC-1, and IL-10), enzymes superoxide dismutase (SOD), and catalase (CAT) analysis, as well as gene expression (TNF-α, IL-1β, RANK, and iNOS) by qRT-PCR. Systemic parameters (weight variation, plasma levels of hepatic enzymes aspartate aminotransferase (AST) and alanine aminotransferase (ALT), creatinine, total alkaline phosphatase (TALP), and bone alkaline phosphatase (BALP) were performed. Histological analysis of the stomach, liver, kidney, and heart was also performed. S. maritima (5 mg/kg) decreased alveolar bone loss, TNF-α and CINC-1 gingival levels, oxidative stress, and transcription of TNF-α, IL1-β, RANK and iNOS genes. It elevated both BALP activity and IL-10 gingival levels.The animals showed no any signs of toxicity. In conclusion, S. maritima reduced pro-inflammatory cytokine production, oxidative stress, and alveolar bone loss in a pre-clinical trial of periodontitis. S. maritima is a potential tool for controlling the development of periodontitis.